Desee, Richard (2019). Climate change and the future of democracy. Massachusetts: Editorial Springer - Villalobos Jiménez, Alonso (2019)
This review analyzes R.S. Deese’s Climate Change and the Future of Democracy in the context of the U.S. withdrawal from the Paris Agreement (2017–2018). Deese argues that climate change threatens democratic ideals and fosters authoritarian, nationalist, and populist responses. He proposes a supranational democratic model capable of restoring trust and enabling coordinated global action. The book critiques authoritarian capitalism and highlights the historical link between militarized nationalism and environmental degradation. Drawing from Cold War scientific advances, Deese advocates for placing climate research at the center of decision-making, emphasizing that liberal democracies must evolve to confront planetary environmental crises.